DESAIN PEMBELAJARAN PERBANDINGAN SENILAI MENGGUNAKAN GUIDED INQUIRY - Rahmasantika, Danty; Prahmana, Rully Charitas Indra (Universitas Papua, 2019)
This study aims to support students' understanding of learning comparative material and determine student learning outcomes incomparable learning through LAS-based guided inquiry learning models. This study uses a research design research method, which was carried out in class VII B SMP N 1 Berbah Sleman. The research instruments used were recording devices, written test sheets, field notes sheets, and questionnaire sheets. The results showed that at the 1st and 2nd meetings, students were seen to be still adapting to the learning design applied. At the next meeting, students can participate in learning activities better. Also, student learning outcomes indicate that the average value obtained by students is 71.57 with Minimum Completeness Criteria (KKM) for a comparison of 70.